2010
DOI: 10.1371/journal.pone.0013820
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Induces Aberrant Amyloid Precursor Protein Processing by Promoting Its Interaction with Endoplasmic Reticulum Chaperone Proteins

Abstract: BackgroundLactic acid, a natural by-product of glycolysis, is produced at excess levels in response to impaired mitochondrial function, high-energy demand, and low oxygen availability. The enzyme involved in the production of β-amyloid peptide (Aβ) of Alzheimer's disease, BACE1, functions optimally at lower pH, which led us to investigate a potential role of lactic acid in the processing of amyloid precursor protein (APP).Methodology/Principal FindingsLactic acid increased levels of Aβ40 and 42, as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…CoA is also a purinergic negative modulator of neuronal acetylcholine release (Cook, Hamilton, & Okwuasaba, ), which is itself impaired in AD (Corkin, ; Richter et al, ). Similarly, alteration of CoA metabolism and its flux through oxidative phosphorylation may reflect alternative and/or compensatory bioenergetic strategies to metabolic stress and insult (Xiang, Xu, & Weigel‐Van Aken, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoA is also a purinergic negative modulator of neuronal acetylcholine release (Cook, Hamilton, & Okwuasaba, ), which is itself impaired in AD (Corkin, ; Richter et al, ). Similarly, alteration of CoA metabolism and its flux through oxidative phosphorylation may reflect alternative and/or compensatory bioenergetic strategies to metabolic stress and insult (Xiang, Xu, & Weigel‐Van Aken, ).…”
Section: Discussionmentioning
confidence: 99%
“…This figure reflects the relevant findings of this study and the biochemical pathways implicated in DS-AD. The pathway interactions suggest a shift in energy metabolism in DS-AD from oxidative phosphorylation to alternate, less efficient means of energy production which may have broad effects on cell membrane integrity, synaptic plasticity, and oxidative stress of CoA metabolism and its flux through oxidative phosphorylation may reflect alternative and/or compensatory bioenergetic strategies to metabolic stress and insult (Xiang, Xu, & Weigel-Van Aken, 2010).…”
Section: T a B L E 2 Metabolic Pathwaysmentioning
confidence: 99%
“…Recently, cell-based studies have demonstrated that incubation of cultured cells with lactic acid induces aberrant amyloid precursor protein processing to increase Aβ40 and 42 peptides (Xiang et al, 2010) and enhances AMPK activation (Chen et al, 2010a). Besides, H 2 O 2 treatment of SH-SY5Y cells was shown to cause not only oxidative stress but also AMPK activation, and such oxidative stress was protected by decreasing AMPK level via gene knockdown (Chen et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium-induced activation of glial cells (Elizabeth et al, 2020) causes conformational changes in neuroenergetics during neuroinflammation by shunting more pyruvate for glycolytic conversion to lactate (Mason, 2017), thereby availing more ATP to reactive astrocyte. Despite the advantage of the metabolic reprogramming, sustained lactate accumulation has been documented to exacerbate amyloidogenesis by promoting molecular interaction between endoplasmic reticulum chaperone and APP (Xiang et al, 2010), which may explain the increase argentophilic bodies around the soma of corticohippocampal neurons. Increase lactate activity, as induced by aluminium in this study, has also been reported to be an indicator of cellular hypoxia and promote cell death (Firth et al, 1995;Koukourakis et al, 2003;Rama Rao and Kielian, 2015), which may justify the observed perturbed corticohippocampal histomorphology.…”
Section: Discussionmentioning
confidence: 99%